Doing Crime: An Analysis of Repetitive Property Offenders' Decision-Making - Tunnell, Kenneth D. (1988)
Over the past two decades social theory and research have focused increasingly on issues of criminal decision-making and deterrence. This inter-disciplinary movement draws from criminology, economics, and psychology, which share common assumptions that point toward a model of rational decision-making. Each body of thought considers criminal decision-making as being no different than non-criminal decision-making. Deciding whether to commit a crime is considered a decision problem, a unique one no less, but a decision that is resolved similarly to other decision problems. The central objective of my research is to enhance our understanding of decision-making, specifically individual career criminal decision-making about whether or not to commit a crime, various alternatives considered in the decision problem, and influences on the decision processes. This dissertation reviews literature on decision-making processes as explicated by perceptual deterrence, economic, and cognitive decision-making theories. They serve as theoretical guidance for this research. I then review previous research on perceptual deterrence and criminal decision-making processes and suggest that both merits or rational decision-making theory and proposed modification of it are debated with little empirical guidance. A purposive sample of 60 adult male repetitive offenders incarcerated in the Tennessee Department of Corrections was selected and interviewed at two different points in time. The interviews focused on each subject's criminal calculus, i.e., their decision-making processes. The findings provide a description of criminal decision-making from which typologies of decision-making were constructed. Offenders were separated into Type I and Type II lambda categories, based on offense frequency, resulting in the following typological constructs: (1) the Type I lambda offender; (2) the non-drug-addicted Type II lambda offender; (3) the drug-addicted Type II lambda offender; (4) the hustling Type II lambda offender. The major conclusion of the study is that criminals do not engage in rational decision-making. The especially do not weigh the possible legal consequences of their actions. Negative consequences are far less influential than positive consequences. This conclusion has implications for deterrence and decision-making theories in that they may not explain adequately the decisions made by repetitive property criminals. The research also addresses the question of offense specialization. My findings are at odds with those who argue for a generalist position suggesting that specialization does occur when criminal activities are viewed over time. Theoretical and methodological suggestions for future research of this nature are offered